PROSPECTS FOR THE DEVELOPMENT OF ESG INVESTING (World Bulletin of Management and Law, 2024)
The article highlights the role and significance of the "ESG" approach in achieving the objectives outlined by the United Nations' sustainable development goals, the criteria investors use for investing companies based on the ESG approach during the transition to a green economy. Additionally, it covers ESG factors and classify related risks, and highlights the benefits of using the ESG approach in the activity of national companies.
Keywords: ESG factors, ESG risks, green economy, financial instruments, green investments, responsible investments, socially responsible investments, green financing, green projects.